Associations Between Serum Inflammatory Markers and Hippocampal Volume in a Community Sample. Issue 9 (22nd August 2016) - Schmidt, Mike F.; Freeman, Kevin B.; Windham, Beverly G.; Griswold, Michael E.; Kullo, Iftikhar J.; Turner, Stephen T.; Mosley, Thomas H.
Abstract : Objectives: To quantify associations between inflammatory biomarkers and hippocampal volume (HV) and to examine effect modification according to sex, race, and age. Design: Cross‐sectional analyses using generalized estimating equations to account for familial clustering; standardized β ‐coefficients adjusted for age, sex, race, and education. Setting: Community cohorts in Jackson, Mississippi and Rochester, Minnesota. Participants: The Genetic Epidemiology Network of Arteriopathy study. Measurements: C‐reactive protein (CRP), interleukin‐6 (IL‐6), and soluble tumor necrosis factor receptors 1 (sTNFR‐1) and 2 (sTNFR‐2) from peripheral blood were measured in a sample of 773 non‐Hispanic whites (61% women, aged 60.2 ± 9.8) and 514 African Americans (70% women, aged 63.9 ± 8.1) who also underwent brain magnetic resonance imaging. Biomarkers were standardized and compared according to sex, race and age with HV. Results: In the full sample, higher sTNFR‐1 and sTNFR‐2 were associated with smaller HV. Each standard deviation (SD) increase in sTNFR‐1 was associated with 59.1 mm 3 (95% confidence interval (CI) = −101.4 to −16.7 mm 3 ) smaller HV and each SD increase in sTNFR‐2 associated with 48.8 mm 3 (95% CI = −92.2 to −5.3 mm 3 ) smaller HV. Relationships were stronger for sTNFR‐2 in men (HV = −116.6 mm 3 for each SD increase, 95% CI = −201.0 to −32.1) than women (HV = −26.0 per SD increase, 95% CI = −72.4–20.5) and sTNFR‐1 in non‐Hispanic whites (HV = −84.7 mm 3 per SD increase, 95% CI = −142.2 to −27.1) than African Americans (HV = −14.1 mm 3 per SD increase, 95% CI = −78.3–50.1). Associations between IL‐6 or CRP and HV were not supported. Conclusion: Higher levels of sTNFRs were associated cross‐sectionally with smaller hippocampi. Longitudinal data are needed to determine whether these biomarkers may help to identify risk of late‐life cognitive impairment.